Pertimbangan Hakim Dalam Memutuskan Perkara Perceraian Bagi Aparatur Sipil Negara Tanpa Surat Izin Atasan Perspektif Teori Maslahah: Studi Kasus Pengadilan Agama Parepare - Mir'ah Thania; Hamang, M. Nasri; Hannani, Hannani; Fikri, Fikri; Darwis, Rizal (Al-Mizan (e-Journal), 2024)
Government Regulation Number 45 of 1990 concerning Marriage and Divorce Permits for Civil Servants in article 3 stipulated that all civil servants intending to divorce had to have prior permission from their superiors or a letter of recommendation from a relevant official. This administrative requirement was mandatory, allowing the judge to consider and decide on divorce cases involving civil servants. This research employed field research with an empirical juridical approach, which was conducted directly to understand the real issues and was then linked to applicable laws, the legal certainty theory, and the maslahah theory (maintaining the objectives of shari'a and achieving benefits/avoiding harms). The research findings concluded that: 1) the divorce requirements in the maslahah theory aimed to reduce the divorce rate among civil servants. Superiors or authorized officials had the right to guide employees to try to preserve their marriages; 2) the Parepare Religious Court granted six months to obtain permission from superiors. If, by the specified deadline, the individual did not have this permission and still wished to divorce, they were required to submit a statement willing to bear the consequences of divorce without the superior's permission. The related consequences were outlined in Government Regulation Number 94 of 2021 on Civil Servant Discipline; 3) there was a connection between the judge's consideration and the maslahah theory. In addition to considering the applicable laws, the judge also took into account aspects of maslahah when making decisions. The maslahah obtained from a formal divorce in the Religious Court included legal certainty and justice in the judge's divorce decree.